The Intermediates in Lewis Acid Catalysis with Lanthanide Triflates. Issue 22 (24th May 2019) - Tripodi, Guilherme L.; Correra, Thiago C.; Angolini, Célio F. F.; Ferreira, Bruno R. V.; Maître, Philippe; Eberlin, Marcos N.; Roithová, Jana
Abstract : Lanthanide triflates are effective Lewis acid catalysts in reactions involving carbonyl compounds due to their high oxophilicity and water stability. Despite the growing interest, the identity of the catalytic species formed in lanthanide catalysed reactions is still unknown. We have therefore used mass spectrometry and ion spectroscopy to intercept and characterize the intermediates in a reaction catalysed by ytterbium and dysprosium triflates. We were able to identify a number of lanthanide intermediates formed in a simple condensation reaction between a C‐acid and an aldehyde. Results show correlation between the reactivity of lanthanide complexes and their charge state and suggest that the triply charged complexes play a key role in lanthanide catalysed reactions. Spectroscopic data of the gaseous ions accompanied by theoretical calculations reveal that the difference between catalytic efficiencies of ytterbium and dysprosium ions can be explained by their different electrophilicity. Abstract : Knoevenagel condensation can be accelerated by addition of Lewis acids. This work shows a number of intermediates along the reaction path catalyzed by ytterbium and dysprosium and compares relative reaction rates. The main conclusion is: the larger the electrostatic field of the Lewis acid, the more activated the intermediates, and the faster the reaction.